Ukraine : Technical Assistance Report-Report on Residential Property Price Index Capacity Development Mission. (IMF Staff Country Reports; Country Report ;, 2019)
A technical assistance (TA) mission was conducted during June 18-22, 2018 to support the State Statistics Service of Ukraine (SSSU) in improving the residential property price indexes (RPPI) for Ukraine. This was the second of a series of SECO2 RPPI-funded TA missions to take place until mid-2019 that will assist in building staff capacity for further development of the RPPI. RPPIs have been identified as critical ingredients for financial stability policy analysis. The indexes are used by policy makers as an input into design of macroprudential policies, that is, those policies aim to reduce systemic risks arising from 'excessive' financial procyclicality (such as asset bubbles). RPPIs are also used by policy makers to inform monetary policy and inflation targeting.